Fundamentals of Entrepreneurship (ENT300) : Taka Cake House / Mohamad Nadeem Arbi … [et al.] - Arbi, Mohamad Nadeem; Arifin, Rafiq Syahmi; Rakawi, Danial Fitri; Abang Mohamad, Abang Hamizan (2018)
Taka Cake House begins since 1986. Taka first branch first set it footprint on Jalan Satok which is a small outlet. And now Taka is having 14 outlets separated in Kuching, Semariang and Kota Samarahan. In addition, the 15th outlet is on the way of completion. The headquarter of this company is located in Batu Kitang, Bau. Taka is one of the most popular outlet in town in delivering the best quality products to the customers in town. Taka Cake House serve all range of products from plain bread to French croissants, traditional layer cakes to popular western cheese cake. Furthermore, the branches of this outlet will start its operation hour from 10am until 9pm depending on the branch operating area.